Knowledge Management in the Brazilian Ceramic Tile Industry & New Challenges Of Competition in the Global Value Chain - Garcia, Renato; Scur, Gabriela (Journal of Knowledge Management Practice, 2010)
This paper has the objective of investigating the role of the knowledge management of the local firms in regards of the new competitive global scenario of the Brazilian ceramic tiles industry. In a more specific way, I focuses on the dynamics of two main local production systems, located in the region of Criciúma, in the state of Santa Catarina and in Santa Gertrudes, in the state of São Paulo. The new organization of global value chain shows a strengthen of the international pattern of competition, especially as the growth of exports of China, which consolidated itself as the main world manufacturer of ceramic tiles, and Spain as well as the decreased share of the Italian industry. Despite the stronger competition in international markets, the Brazilian industry went through a period of expansion, with the simultaneous growth of the domestic market and of exports. This growth reflected itself in a high dynamism of the domestic industry, which relied both on the expansion of the offer of ceramic tiles and on significant changes in the technical-productive parameters of the companies involved. In this process, it should be underlined the importance of some factors which exerted a fundamental role in the creation and dissemination of new knowledge and in fomenting innovative activities by companies, such as the suppliers of glazing materials, the manufacturers of machinery and equipment and the local service-rendering institutions. It should be emphasized that the productive organization of the industry in local production systems had a fundamental role in this process as it facilitated the dissemination and the circulation of new knowledge among all involved. To do that, it is presented the main characteristics of the global chain of the ceramic tile industry and the Brazilian scenario. Later, it is presented some considerations with respect to the dynamics of the Brazilian ceramic tile industry and its insertion in this new competitive international scenario, with special focus on the mechanisms of creation and dissemination of knowledge among local manufacturer.